2020
DOI: 10.3390/ijms21144976
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Urban Particulate Matter on the Ocular Surface and the Incidence of Deleterious Changes in the Cornea, Conjunctiva and Retina in Rats

Abstract: We investigated the time-dependent deleterious ocular changes induced by urban particulate matter (UPM) in vitro and in vivo. UPM treatment decreased human corneal epithelial cell migration and survival. Fluorescein scores were consistently increased by UPM application for 16 weeks. One week of rest at 2 or 4 weeks led to a recovery trend, whereas two weeks of rest at 8 weeks induced no change. UPM treatment decreased the tear film break-up time at 2 weeks, which was thereafter maintained until 16 weeks. No ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…The results also suggested that necrostatin-1 and the silencing of RIPK3 largely prevented oxidative stress-induced RPE death, which established that necrosis is a major type of RPE cell death in response to oxidative stress [43]. More recently, Kang et al [16] demonstrated that long-term exposure to UPM led to anatomical changes in the retina whereas apoptosis did not occur. Although necrostain-1 significantly inhibited annexin V − /PI + cells in the present study, approximately 50% suppressed the increase in UPM-induced necrotic cells by necrostain-1.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results also suggested that necrostatin-1 and the silencing of RIPK3 largely prevented oxidative stress-induced RPE death, which established that necrosis is a major type of RPE cell death in response to oxidative stress [43]. More recently, Kang et al [16] demonstrated that long-term exposure to UPM led to anatomical changes in the retina whereas apoptosis did not occur. Although necrostain-1 significantly inhibited annexin V − /PI + cells in the present study, approximately 50% suppressed the increase in UPM-induced necrotic cells by necrostain-1.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, there has been increasing interest in the harmful effect of UPM on visual systems, which is an organ directly exposed to urban air pollutants [13][14][15]. In addition, some nonclinical studies have demonstrated that exposure to UPM leads to the apoptosis and inflammation of the corneal and conjunctival epithelium in vitro and in vivo [16,17]. More notably, recent studies have shown that the inner part of the eye may also be affected by urban air pollutants, because air pollution leads to systemic disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PM 2.5 can destroy the integrity of the blood-brain barrier; thus, peripheral systemic inflammation easily crosses the barrier and influences the central nervous system [ 55 ]. Similarly, the blood-retina barrier (BRB) is available for diffusion and permeabilization of PM 2.5 , and its function in BRB could potentially play a role in PM 2.5 -mediated retinal pathogenesis [ 7 , 56 , 57 , 58 , 59 , 60 ]. Several epidemiological studies have suggested that ambient PM 2.5 result in increasing prevalence rates of retinal disorders including age-related macular degeneration, diabetic retinopathy and sclerosis of the retina [ 59 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few recent studies demonstrated that PM 2.5 exposure involved in retinal disorders including retinal damage, including retinal atherosclerosis, retinal edema and retinal vessel narrowing [ 57 , 58 , 59 ]. Kang et al [ 7 ] demonstrated that topical exposure to PM 2.5 markedly decreased the NFL/GCL and increased the expression of glial fibrillary acidic protein, a marker of glial activation in response to neural injury [ 60 ]. Furthermore, Chua et al [ 57 ] reported that subjects exposed to higher levels of PM 2.5 were associated with changes in retinal structure features, including RCG and IPL thickness.…”
Section: Discussionmentioning
confidence: 99%